Labour Productivity in Australian Manufacturing: The Impact of Import Competition and Market Structure - Bloch, Harry; Bhattacharya, M.; McDonald, J. (Macmillan India, 2005)
Through altering competitive conditions, globalization can have a significant impact on productivity of the domestic economy. We estimate the impact of import competition and domestic market structure on labour productivity growth in Australian manufacturing using a panel data analysis covering a period of nearly three decades. The results show strong evidence that import competition increases labour productivity growth, particularly in industries where domestic production is highly concentrated.